2017
DOI: 10.2214/ajr.16.17443
|View full text |Cite
|
Sign up to set email alerts
|

Frondlike Synovitis on MRI and Correlation With Polyethylene Surface Damage of Total Knee Arthroplasty

Abstract: The magnitude of frondlike hypertrophied synovitis on MRI is significantly associated with polyethylene surface damage in patients who undergo revision TKA. The finding of severe frondlike synovitis on MR images of patients with TKA should raise the possibility of polyethylene surface damage. However, time since implantation is a stronger predictor of surface damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…A relation was found between the presence of frondlike hypertrophied synovitis on MRI and perioperative findings of loosening due to wear . When these MRI findings were compared with the reference standard perioperative findings, the sensitivity and specificity of the diagnoses varied between 0.94–0.97 and 0.70–0.73 …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…A relation was found between the presence of frondlike hypertrophied synovitis on MRI and perioperative findings of loosening due to wear . When these MRI findings were compared with the reference standard perioperative findings, the sensitivity and specificity of the diagnoses varied between 0.94–0.97 and 0.70–0.73 …”
Section: Resultsmentioning
confidence: 98%
“…These studies reported interrater reproducibilities that were almost excellent (K ≥ 0.80) and moderate (K ≥ 0.60) . One study scored frondlike hypertrophied synovitis, associated with loosening due to wear, and concluded that interrater reproducibility was good (K = 0.72) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations